FUNKCJE ZNAKU TOWAROWEGO W ORZECZNICTWIE EUROPEJSKIEGO TRYBUNAŁU SPRAWIEDLIWOŚCI - Żuraw, Monika (Zeszyty Prawnicze, 2017)
F u n c t io n s o f a T r a d e m a r k A c c o r d in g t o t h e J u r is d ic t io n o f t h e E u r o p e a n C o u r t o f J u s t ic e Summary The scope of protection of the functions fulfilled by trademarks determines most of the issues of the trademark law. The formulation of relevant provisions of the First Directive 89/104/EEC of the Council, of 21 December 1988, to Approximate the Laws of the Member States Relating to Trade Marks („Directive”) leave most of the issues open for interpretation. Therefore, it is the role of the European Court of Justice („ECJ”) to define to what extent the origin, quality and advertising functions should be protected. The article presents in chronological order all ECJ’s verdicts referring to the functions of a trademark issued both before and after entering into force of the Directive. The verdicts above all regard the issues of the trademark infringement, the distinguishing capability of a trademark, exhaustion and the limitations of the right to a trademark. It transpires from the review of the verdicts that ECJ refers most of the issues to the ‘essential function of a trademark’, which is distinguishing goods originating form different enterprises, the concept worked out long before the Directive was introduced. As a result, it is still the origin function that is protected vast more broadly than other functions, which - as it seems - does not meet the needs of the contemporary turnover. Nevertheless, the formulation of most of ECJ’s rulings is so general that it allows future modifications for the benefit of broadening the protection of the quality and advertising functions.